VILLAGE FUND ALLOCATION MANAGEMENT IN SUPPORTING RURAL DEVELOPMENT (CASE STUDY OF NANGANESA VILLAGE AND MANULONDO VILLAGE NDONA DISTRICT, ENDE REGENCY) - Nuraini Ismail; Sabra Wahab Thalib (SEAN Institute, 2022)
The purpose of this study is to determine the process of planning, implementation and accountability of the Village Fund Allocation (ADD) which is based on the applicable rules. The analytical method used in this research is using qualitative descriptive analysis. The data collected in this study are data on the use of Village Fund Allocations in Nanganesa Village and Manulondo Village, Ndona District, Ende Regency from 2012-2015 and data on the planning, implementation and accountability process for using the Village Fund Allocation budget in supporting village development. Based on the results of the study indicate that the planning process